The 2020 report of The Lancet Countdown on health and climate change: responding to converging crises - Watts, Nick; Amann, Markus; Arnell, Nigel; Ayeb-Karlsson, Sonja; Beagley, Jessica; Belesova, Kristine; Boykoff, Maxwell; Byass, Peter; Cai, Wenjia; Campbell-Lendrum, Diarmid; Capstick, Stuart; Chambers, Jonathan; et al. (The Lancet (British edition), 2021)
For the Chinese, French, German, and Spanish translations of the abstract see Supplementary Materials section.TRANSLATIONSFor the Chinese, French, German, and Spanish translations of the abstract see Supplementary Materials section.